Features of adipokine status in hypertensive patients with chronic kidney disease - Filenko, Ya.M.; Korzh, O.M. (KIDNEYS, 2022)
The study aimed at optimization of diagnosis and evaluation of chronic kidney disease (CKD) in hypertensive patients by studying the role of adipokines (leptin, omentin, visfatin, resistin) in patients with hypertension combined with chronic kidney disease. Materials and methods. The study enrolled 100 patients with hypertension of II and III degrees of Stage 2, of which 51 patients were diagnosed with chronic kidney disease. The control group consisted of 20 apparently healthy people. Results. Our study showed that leptin, omentin, resistin, and visfatin levels were significantly higher in patients with essential hypertension (EH) combined with CKD, in contrast to patients with EH without CKD and in the control group. The results of the Kraskel-Wallis dispersion analysis demonstrated that in patients with EH combined with CKD, adipokines significantly correlated with systolic blood pressure (BP), diastolic blood pressure, hypertension degree, body mass index, low-density lipoproteins, thyroglobulin, glomerular filtration rate, creatinine, end-diastolic size, relative wall thickness index, left ventricular myocardial mass, left ventricular myocardial mass index, presence of diastolic dysfunction, type of diastolic function. Conclusions. Hypertensive patients with CKD presented with a significant increase in adipokine levels (leptin, omentin, resistin, visfatin) in the blood compared to patients with EH without CKD (p < 0.05) and apparently healthy individuals (p < 0.05). The data obtained indicate that adipokines (leptin, omentin, resistin, visfatin) have a significant pathogenetic role in patients with hypertension combined with chronic kidney disease.